Perinatal optimisation for periviable birth and outcomes: a 4-year network analysis (2018–2021) across a change in national guidance - Peterson, J.; Smith, D. M.; Johnstone, E. D.; Mahaveer, A. (Frontiers in Pediatrics, 2024)
Introduction The British Association of Perinatal Medicine (BAPM) released their revised framework for extremely preterm infant management in 2019. This revised framework promotes consideration of perinatal optimisation and survival-focused care from 22 weeks gestation onwards. This was a departure from the previous BAPM framework which recommended comfort care as the only recommended management for infants <23 + 0 weeks. Methods Our study evaluates the clinical impact that this updated framework has had across the Northwest of England. We utilised anonymised network data from periviable infants delivered across the region to examine changes in perinatal optimisation practices and survival outcomes following the release of the latest BAPM framework. Results Our data show that after the introduction of the updated framework there has been an increase in perinatal optimisation practices for periviable infants and an 80% increase in the number of infants born at 22 weeks receiving survival-focused care and admission to a neonatal unit. Discussion There remain significant discrepancies in optimisation practices by gestational age, which may be contributing to the static survival rates that were observed in the lowest gestational ages.